Analisis Regresi Multivariat Parameter Hambatan Produktivitas Crushing Plant Dalam Upaya Peningkatan Target Produksi Tambang Emas PT J Resources Bolaang Mongondow Site Bakan Sulawesi Utara - Afrinal Afrinal; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Material processing is one of a very important stage in mining activities. In the processing of the material generally is the reduction of the size of the materials/rocks (comminution) by using the tool crushing. Crushing process should be done gradually because of limited ability to reduce the size of the tool material. Case study research conducted in the area of crushing plant PT J Resources Bolaang Mongondow. The research data consists of working time, idle time, delay time, breakdown and data excavator bucket. From the data analysis that is done then the obtained time total working time line 1 was 32.23 hours, line 2 that is 139.30 hours, line 3 of the 154.03 hours and line 4 with 154.71 hours. With a total barrier line 1 for each of the idle time 253.34 hours, delay time, 42.74 hours and breakdown 31.69 hours. Total line resistance 2 is the idle time 139.30 hours, delay time 75.45 hours and breakdown 24.55 hours. Total resistance line 3 that is idle time 55.01 hours, delay time 68.55 hours and breakdown 82.41 hours. While the total resistance line 4 with the idle time of 53.59 hours, delay time 78.04 hours and breakdown 73.66 hours.Keywords: Multivariat, Productivity, Idle Time, Delay Time, Breakdown